A novel temperature-dependent electrochemical system for electrode materials for time resolved X-ray Diffraction. (1st April 2022) - Huang, Weifeng; Yang, Changchun; Miao, Ning; Lin, Chunfu; Xu, Wei; Marcelli, Augusto; Wei, Hang
Abstract: A novel temperature-dependent electrochemical system has been designed for in-operando time-resolved X-ray diffraction (XRD) study with laboratory X-ray sources. Meanwhile, a dedicated in-situ XRD battery cell has been designed for the in-situ XRD characterization of standard coin cell batteries. Thanks to a shaped Be window, the detection-angle of this in-operando system covers a wide range from 4° to 160° XRD patterns can be collected over the wide temperature range, -30 °C to 100 °C. To test the device, LiMn2 O4 and LiFePO4 electrode materials are measured and in-operando XRD data are collected in electrochemical processes at low and high temperatures. This in-operando system enables original in-operando investigations on the electrode structural evolution of batteries vs. temperature, allowing a deeper understanding of the structural evolution of electrode materials. Graphical abstract: Image, graphical abstract